Implementasi Internet of Things untuk Memonitoring Pengisian dan Penggunaan Air secara Otomatis - Yeris Ari Sandi; Heni Sulistiani (LPPM UBHINUS MALANG, 2025)
This research aims to address efficiency issues in household water management through the implementation of the Internet of Things (IoT) on an automated water reservoir system. The problem identified is the lack of efficient control and monitoring of water replenishment and usage, which often leads to wastage and mismatch with homeowners' needs. This research design adopts an IoT-based approach that enables real-time monitoring and remote control via a web application. The system is also equipped with sensors to detect pipe leaks and monitor water pressure. Analysis of the developed system shows that the device is able to provide accurate and responsive data regarding the condition of the water reservoir, and allows users to control water replenishment as needed. This finding shows a significant improvement in water usage efficiency, as well as reducing potential waste due to leaks and inaccuracies in filling the reservoir. The conclusion of this research is that the designed IoT system can be an effective solution for household water management, providing convenience and better control for users, and has the potential to be widely applied in water management at the home scale.